Implications of prognostic nutritional index in predicting adverse outcomes of uncontrolled diabetic patients: a cohort study of the national health and nutrition examination survey from 2005 – 2018 - Fei Liu; Zhili Jiang; Wei Luo; Yunxiao Yang; Shuai Guo; Jiayi Yi; Geng Shen; Wei Li; Lin Wang; Xiuhuan Chen; Zhaogong Zhi; Tian Liu; et al. (Diabetology & Metabolic Syndrome)
Abstract Background Diabetes mellitus (DM) is a metabolic disorder with increasing prevalence and poor control rates, leading to adverse events. Prognostic nutritional value (PNI) has been identified as a protective factor in DM, but its role in uncontrolled DM remains unclear. Methods This study based on the representative cohort of National Health and Nutrition Examination Survey from 2005 to 2018. A total of 3,313 participants with uncontrolled DM were included in our analyses. PNI was calculated as 5×lymphocyte count (109/L)+ 10×serum albumin (g/L). The endpoints were DM-related and cardiovascular mortality, which were obtained from National Death Index. Univariable and multivariable cox proportional hazard regression were performed to investigate prognostic value of PNI. Results Among 3,313 patients with uncontrolled DM (mean age of 61.75 ± 12.78 years, 53.4% male), PNI level was negatively associated with inflammatory markers and positively associated with metabolic markers of lipid and protein. During a median follow-up of 77 months, 247 DM-related deaths and 205 cardiovascular deaths occurred. Higher PNI levels independently predicted low DM-related (adjusted Hazard ratio [HR] = 0.872, 95% confidence interval [CI] 0.840–0.906, P < 0.001) and cardiovascular mortality (adjusted HR = 0.872, 95% CI 0.834–0.912, P < 0.001). The prognostic value of PNI significantly varied across different DM treatment conditions, which was more pronounced in patients receiving antidiabetic treatments (adjusted HR: insulin + oral antidiabetic drugs [OADs]: 0.832; insulin: 0.863; OADs: 0.894, all adjusted P < 0.001), but was absent in those without antidiabetic treatment. Conclusions A higher PNI level is an independent protective predictor for DM-related and cardiovascular mortality in uncontrolled DM patients. Evaluation of PNI level in uncontrolled DM patients could conduce to stringent intervention. Improvement of PNI could enhance the effective of antidiabetic therapy, especially the insulin therapy, and reduce DM-related mortality.